2011
DOI: 10.1111/j.1551-2916.2010.04352.x
|View full text |Cite
|
Sign up to set email alerts
|

An Advanced Single Particle Model for C3S and Alite Hydration

Abstract: The hydration behavior of portland cement phases continues to be debated with new insights fueling the controversy. What causes the induction period? What initiates acceleration? What causes the onset and rapid decrease in reaction rate post peak? Does diffusion play a role and what causes low, but sustained reaction rates for long periods of time? Recent modeling efforts suggest that boundary nucleation and growth can explain at least some of the observations and that such occurs in a “limited reaction volume… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(16 citation statements)
references
References 13 publications
0
16
0
Order By: Relevance
“…Compared to many recently published models [6,26,31] , the model proposed in this study is rather simplified with a minimum number of independent parameters. Biernacki and Xie have extracted a much larger number of parameters (12 fixed and eight adjustable) by adopting a mass continuity-based continuum approach to model C 3 S hydration [31] .…”
Section: Modeling the Total Hydration Kineticsmentioning
confidence: 98%
See 2 more Smart Citations
“…Compared to many recently published models [6,26,31] , the model proposed in this study is rather simplified with a minimum number of independent parameters. Biernacki and Xie have extracted a much larger number of parameters (12 fixed and eight adjustable) by adopting a mass continuity-based continuum approach to model C 3 S hydration [31] .…”
Section: Modeling the Total Hydration Kineticsmentioning
confidence: 98%
“…Such behavior may imply that nucleation at new sites is less likely to happen during the " growth period " as it seems easier for the ions to attach to C-S-H surfaces than C 3 S surfaces. Even if new nucleation does occur, it has been demonstrated that early hydration kinetics is much more sensitive to the amount of instantaneously formed nuclei than the subsequent nucleation rate [31] . The model presented here only investigates the case of site-saturated nucleation.…”
Section: Modeling the Nucleation And Growth Controlled Stagementioning
confidence: 99%
See 1 more Smart Citation
“…The large CH crystals formed in alite paste may completely stop the hydration of certain C 3 S particles enclosed inside. It should also be noted that the method used here to account for inter-particle interactions is different from that introduced in [12] , though they are based on similar principles.…”
Section: Portland Cement Paste Hydrationmentioning
confidence: 97%
“…If one assumes particles of all sizes behave like the system average, as suggested by Biernacki and Xie [12] , then Equation (8) can be applied to individual cement particles and becomes compatible with the particle-based models. Hence, for Portland cement paste hydration, Equation (2) becomes…”
Section: Portland Cement Paste Hydrationmentioning
confidence: 98%